Impact of Violence against Children in the Family Related To Law Number 23 Year 2004 Concerning Deletion of Violence in Household - Muhammad Rizal; Fathul Djannah (Budapest International Research and Critics University, 2020)
The aim of the study is to find out the impact of violence against children in the family related. This research is a normative juridical study, the approach of which is a normative legal approach, which examines the rules of law relating to factors that cause violence against children in the household, the impact of violence on children in the household, efforts to protect children victims of violence in the home stairs. The result shows that the Factors that cause violence against children in the household are Psychodynamics models the occurrence of violence is caused by the lack of